Learning attributes of summa cum laude students: Experience of a Nigerian university - Jonathan A. Odukoya; David O. Omole; Aaron A. Atayero; Joke A. Badejo; Segun I. Popoola; Temitope M. John; Emeka Ucheaga (Cogent Education, 2018)
In this project, 276 students at a private university in Nigeria completed a survey concerned with their personal attributes and study dispositions. First class (summa cum laude) students were compared with third class (less successful) students. Differences were not found in their goal setting habits, and declaration of healthiness. The third class students indicated higher levels of participation in sporting activities. The first class students reported higher levels of spirituality and Bible reading. When asked about their use of basic study skills, the two groups reported fairly similar levels, but then they diverged strongly on deeper learning approaches, with the first class students reporting higher levels of deep study strategies.